2015
DOI: 10.1111/ced.12489
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidant enzyme activity and antioxidant capacity in patients with newly diagnosed pemphigus vulgaris

Abstract: Patients with PV have significantly higher antioxidant enzyme activities and lower total antioxidant capacity compared with HCs. These data indicate the importance of improving antioxidant level in patients with pemphigus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 22 publications
3
24
0
Order By: Relevance
“…Similar results were obtained in a study conducted by Javanbakht M among patients of senile cataract and found that the statistically higher prevance of raised serum sodium levels in patients of senile cataract. Most of characteristics of their study were similar to present study (8).…”
Section: Discussionsupporting
confidence: 85%
“…Similar results were obtained in a study conducted by Javanbakht M among patients of senile cataract and found that the statistically higher prevance of raised serum sodium levels in patients of senile cataract. Most of characteristics of their study were similar to present study (8).…”
Section: Discussionsupporting
confidence: 85%
“…However, CAT destroys H 2 O 2 , generating water and oxygen. It reported that otoimmune disorders like patients with PV have significantly higher antioxidant enzyme activities (25). Our study demonstrated an increase in SOD and CAT activities.…”
Section: Discussionsupporting
confidence: 68%
“…She also received instructions on increasing antioxidant food as fruits, emphasizing the exclusion of foods such as: garlic, onions, cherries, blackberries, black pepper, red wine, tea, coffee, because they have a direct influence on the development of the disease. 8 In the first assessment, the patient presented weight (94,5Kg decreasing to 88.7 (BMI for overweight) at reassessment; height (1.64 m), with Body Mass Index (BMI) indicating a grade II obesity (BMI=35.13 kg/m²) initially, high WC (107.5cm) and 97 cm after, HP (122 cm) going to 116.5, AC indicating obesity (35.05 cm), subsequently 33cm (overweight) and waist-hip ratio (WHR) (0.88 cm), decreasing to 0.83, indicating, in both assessments, high risk for cardiovascular diseases (Table 01). In the evaluation of the InBody Bioimpedance, her results improved, with values on the body composition with weight reduction preserving the skeletal muscle mass and reducing fat mass (Graph 01).…”
Section: Description Of the Case And Resultsmentioning
confidence: 99%
“…By analyzing her food routine, the research subject had relevant changes in her habits, such as greater consumption of antioxidants, which was very important, since she demonstrated the need to improve the level of antioxidants. 8 A study showed that 43 patients newly diagnosed with PV presented activities of antioxidant enzymes significantly higher and lower total antioxidant capacity.…”
Section: Discussionmentioning
confidence: 99%